Psychometric evaluation of the Malay version of the multidimensional Beck Youth Inventories-2 (BYI-2 Malay): measuring self-concept, anxiety, depression, anger, and disruptive behaviour among adolescents in sheltered homes - Ding, Wai Eng; Tan, Kit Aun; Fam, Jia Yuin; Mukhtar, Firdaus; Lye, Munn Sann; Awang, Hamidin; Munawar, Khadeeja (Universiti Putra Malaysia Press, 2021)
The purpose of this study was to evaluate the psychometric properties of the Malay version of the Beck Youth Inventories-Second Edition (BYI-2 Malay) in a sample of adolescents living in the nongovernment-run sheltered homes. In this study, 300 adolescents completed the BYI-2 Malay, the Beck Depression Inventory-Malay (BDI-Malay), the Beck Anxiety Inventory-Malay (BAI-Malay), the Automatic Thoughts Questionnaire-Malay (ATQMalay), and the Rosenberg Self-Esteem Scale-Malay (RSES-Malay). The internal consistency estimates for the BYI-2 Malay scales, as measured by Cronbach’s alpha, were excellent: .86 for self-concept, .89 for anxiety, .92 for depression, .92 for anger, and .92 for disruptive behaviours. The five-factor model of the BYI-2 Malay (i.e., Self-Concept, Anxiety, Depression, Anger, and Disruptive Behaviour) showed a good fit to the data. Evidence for concurrent validity was established between the BYI-2 Malay Self-Concept scale and the RSES-Malay (r = .41), between the BYI-2 Malay Anxiety scale and the BAI-Malay (r = .60), and between the BYI-2 Malay Depression scale and the BDI-Malay (r = .69). The evidence for convergent validity was established between the BYI-2 Malay Anger scale and the ATQ-Malay (r = .71), and between BYI2 Malay Disruptive Behaviour scale and the ATQ Malay (r =.52). The present findings shed light on the utility of the BYI-2 Malay in aiding clinicians as well as therapists for identifying multiple symptoms of social and emotional problems in adolescents.